Desilla, Louisa. 2025. Translation and Pragmatics. Routledge. ISBN 978-1-032-08150-2 - Neagoe, Ionela Denisa (Complutense Journal of English Studies, 2025)
Louisa Desilla’s Translation and Pragmatics: Theories and Applications provides a comprehensive yet accessible insight into the relationship between pragmatics and translation. This review outlines the structure and pedagogical approach of the book, focusing on how Desilla translates theoretical insights into practical activities designed for students and early-career professionals. The review compares this work with other key contributions in the field, emphasizing its value in bridging theory and practice in audiovisual translation contexts.